Clinical Use of Continuous Performance Tests to Diagnose Children With ADHD. Issue 6 (April 2019) - Park, Jangho; Kim, Changyoon; Ahn, Joon-Ho; Joo, Yeonho; Shin, Min-Sup; Lee, Hyun-Jeong; Kim, Hyo-Won
Objective: This study evaluated the diagnostic application of continuous performance tests in children with ADHD.Method: We recruited 114 children (aged 6-12) from August 2012 to May 2014. Seventy-nine children were diagnosed with ADHD and 35 were enrolled as controls. The Advanced Test of Attention (ATA) was administered to all participants.Results: There were significant between-group differences for the frequency distribution of four ATA variables. The ATA criteria yielded a diagnostic sensitivity and specificity of 84.8% and 45.7%, respectively. Discriminant analysis revealed that auditory reaction time variability and visual commission errors helped distinguish between the groups. Discriminate functions indicated correct classification of 64.9% children. ADHD children tended to have lower intra-class correlation coefficients.Conclusion: Our results suggest that the ATA distributions of ADHD individuals may differ from the general population; in addition, the ATA results could not independently diagnose ADHD. Therefore, they should be considered carefully before diagnosis.